A high-throughput power battery positive electrode material and preparation method thereof

By dividing into high nickel phase and low nickel phase in the crystal structure of the positive electrode material of the power battery, the problem of lithium-nickel mixed discharge phenomenon is solved, and the charging and discharging performance and cycle life of the battery are significantly improved, especially under fast charging conditions, which shows more Good battery performance.

CN119176589BActive Publication Date: 2025-02-21湖南镕锂新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411689250.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In power lithium batteries, the increase in nickel content leads to a mixed discharge phenomenon of lithium nickel, affecting the charging and discharging performance and cycle life of the battery, especially under fast charging conditions.

Method used

By dividing into high nickel phase and low nickel phase in the crystal structure of the positive electrode material of the power battery, nickel ions tend to be transferred in different nickel phases to avoid nickel ions from occupying the position of lithium ions, thereby reducing the mixed discharge of lithium nickel. The method includes dividing the nickel source into two portions for different treatments, forming a cladding layer and modifying zirconium dioxide particles, and changing the distribution and diffusion path of the nickel element.

Benefits of technology

It effectively reduces the occurrence of nickel-lithium mixed discharge phenomenon, improves the charging and discharging performance and cycle life of the battery, and especially shows a longer battery life under fast charging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a high-throughput power battery positive electrode material and a preparation method thereof, which belongs to the technical field of new energy battery electrode materials. Among them, the preparation method of the high-throughput power battery positive electrode material includes: weighing the raw materials, dividing the nickel source into two parts of unequal weight; respectively configuring the nickel source, cobalt source, and manganese source of large weight portions into solutions, mixing the solutions of the three to form a mixed salt solution to prepare a nickel-cobalt-manganese precursor; sintering the nickel-cobalt-manganese precursor with a lithium source for the first time; configuring the nickel source of small weight portions into a nickel salt solution to prepare a nickel hydroxide precipitate; modifying the nickel hydroxide precipitate to prepare a nickel hydroxide precipitate with a coating layer modified with zirconium dioxide on the surface; sintering the modified nickel hydroxide with the first sintering product for the second time to obtain a high-throughput power battery positive electrode material. The positive electrode material prepared by the above method can reduce the nickel-lithium mixed discharge phenomenon, has high-throughput characteristics, and can be widely used in fast-charging power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery electrode materials, and in particular to a high-throughput power battery positive electrode material and a preparation method thereof. Background Art

[0002] Traditional fuel-powered vehicles are highly dependent on fossil fuels such as oil. As global energy consumption continues to rise, fossil fuel reserves are gradually decreasing, and the energy crisis is becoming increasingly prominent. The search for alternative clean energy sources has become a key direction for global energy development. Electric vehicles, as electric-powered transportation, have enormous potential to reduce reliance on fossil fuels. The range of electric vehicles is a key concern for consumers, and improving the energy density of power batteries is key to increasing range. The performance of cathode materials directly determines the energy density of power batteries, so developing cathode materials with high specific capacity and high voltage is a key approach to improving the energy density of power batteries.

[0003] Currently, the most widely commercialized cathode materials for lithium-ion batteries include lithium cobalt oxide, lithium iron phosphate, and ternary materials. Among them, lithium cobalt oxide is relatively expensive, while lithium iron phosphate has a relatively low gram-to-gram capacity. Ternary materials (Li(NiCoMn)O2 or Li(NiCoAl)O2) are widely used in power lithium batteries due to their manageable costs, high energy density, good cycle performance, and long cycle life.

[0004] In NCM ternary materials, nickel serves to increase the material's volumetric energy density. As the nickel content increases, the specific capacity of the ternary material increases accordingly. For example, upgrading from the common NCM523 (nickel, cobalt, and manganese ratio of 5:2:3) to NCM811 (nickel, cobalt, and manganese ratio of 8:1:1) significantly improves specific capacity. However, increasing the nickel content can easily lead to lithium-nickel mixing. During the charge and discharge process, some nickel ions will occupy the space between lithium ions, hindering the normal transmission of lithium ions. This not only affects the battery's charge and discharge performance, but also accelerates capacity decay and reduces cycle life.

[0005] Especially with the current increasing consumer demand for fast-charging batteries, manufacturers face the primary technical challenge of developing fast-charging batteries: the exacerbation of lithium-nickel mixing caused by continuous rapid charging. To ensure the performance of fast-charging batteries, it is necessary to reduce the occurrence of lithium-nickel mixing. Summary of the Invention

[0006] In order to solve the problems mentioned in the background technology, the high-throughput power battery positive electrode material provided by the present invention uses a special process method to divide the internal crystal structure of the positive electrode material into a high-nickel phase and a low-nickel phase. Nickel ions tend to be transferred in different nickel phases, avoiding nickel ions occupying the position of lithium ions, effectively reducing the occurrence of lithium-nickel mixing phenomenon, and the positive electrode material can be widely used in fast-charging batteries.

[0007] Specifically:

[0008] A method for preparing a high-throughput power battery positive electrode material, comprising the following steps:

[0009] Step 1, weighing the nickel source, cobalt source, manganese source and lithium source, the nickel source is divided into two parts of unequal weight, set aside;

[0010] Step 2: Prepare solutions of nickel source, cobalt source and manganese source in large weight portions, and mix the three solutions to form a mixed salt solution; add the reaction base liquid to the reactor, and dropwise add the mixed salt solution, precipitant solution and complexing agent solution into the reactor at the same time under stirring to react, and control the reaction pH value to be 10-12. After the reaction is completed, filter to separate the precursor, wash and dry it for later use;

[0011] Step 3: Evenly mix the precursor and the lithium source and perform a first sintering to obtain a first sintered product;

[0012] Step 4: A small amount of nickel source is prepared into a nickel salt solution; a reaction base solution is added to a reactor, and the nickel salt solution, precipitant solution, and complexing agent solution are simultaneously added dropwise into the reactor under stirring to react, and the reaction pH value is controlled at 10 to 12. After the reaction is completed, the nickel precipitate is filtered to separate, and the nickel precipitate is washed, dried, and then used for standby use;

[0013] Step 5: Add the nickel precipitate to the catechol solution, adjust the solution to alkalinity, and react under stirring. After the coating is completed, slowly add the zirconium dioxide suspension under stirring to continue the reaction. After the reaction is completed, filter and separate the solid, wash, dry and set aside.

[0014] Step 6: Evenly mix the solid product obtained in step 5 and the first sintered product obtained in step 3 and sinter them to obtain a high-throughput power battery positive electrode material.

[0015] In step 1, a nickel source, a cobalt source, and a manganese source are weighed according to a molar ratio of nickel, cobalt, and manganese of 5 to 8:1 to 2:1 to 3; a lithium source is weighed according to a molar ratio of lithium to the total molar number of nickel, cobalt, and manganese of 1 to 1.1:1; the nickel source is divided into two parts of unequal weight, wherein the weight ratio of the larger weight part to the smaller weight part is 7 to 9:1; nickel sulfate or nickel nitrate is selected as the nickel source, cobalt sulfate or cobalt nitrate is selected as the cobalt source, manganese sulfate or manganese nitrate is selected as the manganese source, and lithium carbonate is selected as the lithium source;

[0016] In step 2, the concentration of the nickel source solution is 1-1.5 mol / L; the concentration of the cobalt source solution is 0.8-1 mol / L; and the concentration of the manganese source solution is 1-1.2 mol / L.

[0017] Furthermore, in step 2 and step 4,

[0018] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 1% to 3%, and the mass concentration of ammonia water is 25% to 28%;

[0019] Precipitant solution configuration: sodium hydroxide aqueous solution with a mass concentration of 25% to 30%;

[0020] Complexing agent solution preparation: ammonia water with a mass concentration of 15% to 25%.

[0021] Furthermore, in step 2, the mixed salt solution is added at a rate of 5 to 10 L / min, the precipitant solution is added at a rate of 10 to 20 L / min, and the complexing agent solution is added at a rate of 5 to 20 L / min until the mixed salt solution is completely added.

[0022] Furthermore, in step three, the first sintering temperature is 500-550°C, the furnace temperature is first raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 10-12 hours; in step six, the second sintering temperature is 600-700°C, the furnace temperature is first raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 8-10 hours.

[0023] Furthermore, in step 4, the nickel salt solution is added at a rate of 1 to 3 L / min, the precipitant solution is added at a rate of 2 to 6 L / min, and the complexing agent solution is added at a rate of 1 to 6 L / min, and the nickel salt solution is added dropwise until the nickel salt solution is completely added.

[0024] Furthermore, in step 5, the catechol solution is prepared by dissolving catechol in a mixed solution of deionized water and ethanol in a volume ratio of 1 to 2:1, with a concentration of the catechol solution of 1 to 2 g / L; and a weight ratio of catechol to nickel precipitate of 0.1 to 0.5:1;

[0025] Preparation of zirconium dioxide suspension: disperse nano-scale zirconium dioxide in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.1-0.2:1; the weight ratio of zirconium dioxide to deionized water is 1:40-80.

[0026] Furthermore, in step five, the coating reaction temperature is 30-50° C., and the reaction time is 8-12 h; the zirconium dioxide modification reaction temperature is 40-60° C., and the reaction time is 4-6 h.

[0027] In addition, the present invention also provides a high-throughput power battery positive electrode material, which is prepared using the above-mentioned preparation method.

[0028] Compared with the prior art, the present invention has the following advantages:

[0029] 1. The preparation method of the high-throughput power battery positive electrode material provided by the present invention divides the nickel source into two parts of different sizes and performs different treatments; first, a large amount of nickel source is mixed with a cobalt source and a manganese source to prepare a nickel-cobalt-manganese hydroxide precipitate and sintered with lithium carbonate for the first time, and then a small amount of nickel source is used alone to prepare a nickel hydroxide precipitate, which is then subjected to special treatments such as catechol coating and zirconium dioxide particle modification before participating in the second sintering; during the second sintering process, the coating layer of the small amount of nickel precipitate and the surface-modified zirconium dioxide particles synergistically change the local reaction environment and element diffusion path, so that the small amount of nickel element is distinguished from the large amount of nickel element in the crystal, and the second sintering product retains the layer The main crystal form of the positive electrode material has a nickel-like structure, but due to the special treatment of a small amount of nickel precipitation, structural adjustments or changes occur in local areas. This different treatment method makes the distribution of nickel elements different during the two sintering processes, and a high-nickel phase and a low-nickel phase are formed inside the crystal. The reason for the occurrence of nickel-lithium mixed arrangement is that the main undesirable migration direction of nickel ions is toward the lithium layer. The present invention forms a high-nickel phase and a low-nickel phase inside the positive electrode material crystal, guiding the nickel ions to perform more internal re-balance migration between the high-nickel phase and the low-nickel phase, so that the migration trend of nickel ions is more inclined from the high-nickel phase to the low-nickel phase rather than to the lithium layer, effectively reducing the harmful migration of nickel ions to the lithium layer, thereby inhibiting the occurrence of nickel-lithium mixed arrangement.

[0030] 2. The preparation method of the high-throughput power battery positive electrode material provided by the present invention has interfacial energy between the high-nickel phase and the low-nickel phase in the positive electrode material crystal, thereby preventing nickel ions from easily migrating. Therefore, even if the battery undergoes multiple charge and discharge cycles, the high-nickel phase and the low-nickel phase of the positive electrode material still exist. The migration trend of nickel ions from the high-nickel phase to the low-nickel phase is higher than the migration trend of nickel ions from the nickel phase to the lithium layer, ensuring the long-term effectiveness of the positive electrode material in suppressing nickel-lithium mixing.

[0031] 3. The present invention provides a method for preparing a high-throughput power battery positive electrode material. Catechol easily undergoes an oxidative polymerization reaction under alkaline conditions. As the reaction proceeds, the degree of polymerization continues to increase, and eventually a relatively high molecular weight polymer is formed, which is tightly adsorbed on the surface of the nickel precipitate, thereby forming a coating layer. In addition, the phenolic hydroxyl groups on the catechol polymer can undergo a coordination chemical reaction with the metal ions on the surface of the zirconium dioxide particles to form a coordination bond, further enhancing the bonding force between the zirconium dioxide particles and the catechol coating, so that the zirconium dioxide particles are more firmly modified on the coating layer. During the sintering process, the catechol polymer coating and the zirconium dioxide particles will hinder the diffusion of nickel from a small amount of nickel precipitate, making it impossible for nickel to be evenly distributed in the crystal, thereby ensuring the formation of high-nickel phase and low-nickel phase. DETAILED DESCRIPTION

[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0033] In order to facilitate those skilled in the art to implement the present invention, some of the reagents used in the examples and comparative examples are now described:

[0034] Nickel source: nickel sulfate, Wuhan Jiyesheng Chemical;

[0035] Cobalt source: cobalt sulfate heptahydrate, Wuhan Jiyesheng Chemical;

[0036] Manganese source: manganese sulfate monohydrate, Wuhan Jiyesheng Chemical;

[0037] Lithium source: lithium carbonate, Wuhan Jiyesheng Chemical;

[0038] Sodium hydroxide: analytical grade, Langfang Huachen Chemical;

[0039] Ammonia: 25% ammonia, analytical grade, Shandong Shengze Chemical;

[0040] Ethanol: Shandong Xinyingshun New Materials;

[0041] Catechol: Jinan Blue Jazz Trading;

[0042] Zirconium dioxide: Langfang Pengcai Fine Chemicals.

[0043] Example 1

[0044] A method for preparing a high-throughput power battery positive electrode material, comprising the following steps:

[0045] S1. Weigh a nickel source, a cobalt source, and a manganese source at a molar ratio of 8:1:1 between nickel, cobalt, and manganese; weigh a lithium source at a molar ratio of 1.1:1 between the molar number of lithium and the total molar number of nickel, cobalt, and manganese; divide the nickel source into two parts of unequal weight, wherein the weight ratio of the larger part to the smaller part is 9:1;

[0046] S2. Preparation of a large weight portion of nickel source solution: dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0047] Preparation of cobalt source solution: dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0048] Manganese source solution preparation: dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L;

[0049] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0050] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0051] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0052] S3. Open a reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, add the mixed salt solution of nickel, cobalt and manganese source solution, the precipitant solution, and the complexing agent solution dropwise into the reactor to react. The dropping speed of the mixed salt solution is 10L / min, the dropping speed of the precipitant solution is 20L / min, and the dropping speed of the complexing agent solution is 20L / min. Add dropwise until the mixed salt solution is added completely. The reaction pH value is controlled at 12 and the reaction is carried out for 20h. After the reaction is completed, filter and separate the precursor, wash, dry and set aside.

[0053] S4, the precursor and the lithium source are mixed evenly and sintered for the first time, the furnace temperature is first raised to a sintering temperature of 550°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 12 hours to obtain a first sintered product;

[0054] S5. Preparation of a small weight portion of nickel source solution: dissolving nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0055] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0056] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0057] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0058] S6. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction bottom liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor. The dropping rate of the nickel salt solution is 3L / min, the dropping rate of the precipitant solution is 6L / min, and the dropping rate of the complexing agent solution is 6L / min. The nickel salt solution is added dropwise until the nickel salt solution is added completely, and the reaction is carried out. The reaction pH value is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, washed, and dried for standby use.

[0059] S7. Preparation of catechol solution: dissolve catechol in a mixed solution of deionized water and ethanol in a volume ratio of 2:1, with a concentration of 2 g / L; the weight ratio of catechol to nickel precipitate is 0.5:1;

[0060] Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide is dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.2:1; the weight ratio of zirconium dioxide to deionized water is 1:80;

[0061] S8, adding the nickel precipitate to the catechol solution, adding sodium hydroxide to adjust the pH value of the solution to 9, reacting under the conditions of stirring at 400 rpm and 50° C. for 12 hours, and after the coating is completed, slowly adding the zirconium dioxide suspension under the conditions of stirring at 400 rpm and 60° C. to continue the reaction for 6 hours, and after the reaction is completed, filtering and separating the solid, washing, and drying it for later use;

[0062] S9. Ball mill the solid product of S8 and the first sintering product. The ball milling time is set to 4 hours, and the ball milling speed is controlled at 400 rpm. After mixing evenly, the furnace temperature is raised to a sintering temperature of 700°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 10 hours to obtain a high-throughput power battery positive electrode material.

[0063] Example 2

[0064] A method for preparing a high-throughput power battery positive electrode material, comprising the following steps:

[0065] S1. Weigh a nickel source, a cobalt source, and a manganese source at a molar ratio of nickel, cobalt, and manganese of 5:2:3; weigh a lithium source at a molar ratio of lithium to the total molar ratio of nickel, cobalt, and manganese of 1:1; divide the nickel source into two parts of unequal weight, wherein the weight ratio of the larger part to the smaller part is 7:1;

[0066] S2. Preparation of a large nickel source solution: dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0067] Preparation of cobalt source solution: dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 0.8 mol / L;

[0068] Manganese source solution preparation: dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0069] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 1%, and the mass concentration of ammonia water is 25%;

[0070] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 25%;

[0071] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 15;

[0072] S3. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, the mixed salt solution of the nickel, cobalt and manganese source solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor for reaction. The dropping speed of the mixed salt solution is 5L / min, the dropping speed of the precipitant solution is 10L / min, and the dropping speed of the complexing agent solution is 5L / min. The mixture is added dropwise until the addition of the mixed salt solution is completed. The reaction pH value is controlled at 10 and the reaction is carried out for 12h. After the reaction is completed, the precursor is filtered to separate, washed, and dried for later use.

[0073] S4, the precursor and the lithium source are mixed evenly and sintered for the first time, the furnace temperature is first raised to a sintering temperature of 500° C. at a heating rate of 2° C. / min, and then the sintering time is maintained at the set temperature for 10 h to obtain a first sintered product;

[0074] S5. Preparation of a small amount of nickel source solution: dissolving nickel sulfate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0075] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 1%, and the mass concentration of ammonia water is 25%;

[0076] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 25%;

[0077] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 15%;

[0078] S6. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction bottom liquid. Under the conditions of stirring at 200rpm and a temperature of 40°C, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor. The dropping rate of the nickel salt solution is 1L / min, the dropping rate of the precipitant solution is 2L / min, and the dropping rate of the complexing agent solution is 1L / min. The nickel salt solution is added dropwise until the nickel salt solution is added completely, and the reaction is carried out. The reaction pH value is controlled at 10, and the reaction is carried out for 12h. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, washed, and dried for standby use.

[0079] S7. Preparation of catechol solution: dissolve catechol in a 1:1 volume ratio of deionized water and ethanol to obtain a catechol solution concentration of 1 g / L; the weight ratio of catechol to nickel precipitate is 0.1:1;

[0080] Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide is dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.1:1; the weight ratio of zirconium dioxide to deionized water is 1:40;

[0081] S8, adding the nickel precipitate to the catechol solution, adding sodium hydroxide to adjust the pH value of the solution to 8, reacting under the conditions of stirring at 200 rpm and a temperature of 30° C. for 8 hours, and after the coating is completed, slowly adding the zirconium dioxide suspension under the conditions of stirring at 200 rpm and a temperature of 40° C. to continue the reaction for 4 hours. After the reaction is completed, filtering and separating the solid, washing, and drying it for later use;

[0082] S9. Ball mill the solid product of S8 and the first sintering product. The ball milling time is set to 2 hours, and the ball milling speed is controlled at 200 rpm. After mixing evenly, the furnace temperature is raised to a sintering temperature of 600°C at a heating rate of 2°C / min, and then the sintering time is maintained at the set temperature for 8 hours to obtain a high-throughput power battery positive electrode material.

[0083] Example 3

[0084] A method for preparing a high-throughput power battery positive electrode material, comprising the following steps:

[0085] S1. Weigh a nickel source, a cobalt source, and a manganese source at a molar ratio of nickel, cobalt, and manganese of 7:1:2; weigh a lithium source at a molar ratio of lithium to the total molar ratio of nickel, cobalt, and manganese of 1:1; divide the nickel source into two parts of unequal weight, wherein the weight ratio of the larger part to the smaller part is 8:1;

[0086] S2. Preparation of a large nickel source solution: dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.3 mol / L;

[0087] Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 0.9 mol / L;

[0088] Manganese source solution preparation: dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.1 mol / L;

[0089] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 2% and the mass concentration of ammonia water of 25%;

[0090] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 27%;

[0091] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 20%;

[0092] S3. Open a reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, the mixed salt solution of the nickel, cobalt and manganese source solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor for reaction. The dropping speed of the mixed salt solution is 7L / min, the dropping speed of the precipitant solution is 15L / min, and the dropping speed of the complexing agent solution is 10L / min. The mixture is added dropwise until the addition of the mixed salt solution is completed. The reaction pH value is controlled at 11.2 and the reaction is carried out for 16h. After the reaction is completed, the precursor is filtered to separate, washed, and dried for later use.

[0093] S4, the precursor and the lithium source are mixed evenly and sintered for the first time, the furnace temperature is first raised to a sintering temperature of 520°C at a heating rate of 3°C / min, and then the sintering time is maintained at the set temperature for 11 hours to obtain a first sintered product;

[0094] S5. Preparation of a small amount of nickel source solution: dissolving nickel sulfate in deionized water to prepare a solution with a concentration of 1.3 mol / L;

[0095] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 2% and the mass concentration of ammonia water of 25%;

[0096] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 27%;

[0097] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 20%;

[0098] S6. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction bottom liquid. Under the conditions of stirring at 300rpm and a temperature of 40°C, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor. The dropping rate of the nickel salt solution is 2L / min, the dropping rate of the precipitant solution is 4L / min, and the dropping rate of the complexing agent solution is 4L / min. The nickel salt solution is added dropwise until the nickel salt solution is added. The reaction is carried out, and the reaction pH value is controlled at 11. The reaction is carried out for 15h. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, washed, and dried for standby use.

[0099] S7. Preparation of catechol solution: dissolve catechol in a mixture of deionized water and ethanol in a volume ratio of 1.5:1, with a concentration of 1.5 g / L; and a weight ratio of catechol to nickel precipitate of 0.3:1.

[0100] Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide is dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.1:1; the weight ratio of zirconium dioxide to deionized water is 1:60;

[0101] S8, adding the nickel precipitate to the catechol solution, adding sodium hydroxide to adjust the pH value of the solution to 8.5, reacting under the conditions of stirring at 300 rpm and a temperature of 40° C. for 10 hours, and after the coating is completed, slowly adding the zirconium dioxide suspension under the conditions of stirring at 300 rpm and a temperature of 50° C. to continue the reaction for 5 hours. After the reaction is completed, the solid is filtered and separated, washed, and dried for later use;

[0102] S9. Ball mill the solid product of S8 and the first sintering product. The ball milling time is set to 3 hours, and the ball milling speed is controlled at 300 rpm. After mixing evenly, the furnace temperature is raised to a sintering temperature of 650°C at a heating rate of 3°C / min, and then the sintering time is maintained at the set temperature for 8 hours to obtain a high-throughput power battery positive electrode material.

[0103] Comparative Example 1

[0104] A method for preparing a positive electrode material for a battery, comprising the following steps:

[0105] S1. Weigh a nickel source, a cobalt source, and a manganese source at a molar ratio of 8:1:1 for nickel, cobalt, and manganese; and weigh a lithium source at a molar ratio of 1.1:1 for the total molar number of lithium to the total molar number of nickel, cobalt, and manganese;

[0106] S2. Nickel source solution preparation: dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0107] Preparation of cobalt source solution: dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0108] Manganese source solution preparation: dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L;

[0109] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0110] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0111] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0112] S3. Open a reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, add the mixed salt solution of nickel, cobalt and manganese source solution, the precipitant solution, and the complexing agent solution dropwise into the reactor to react. The dropping speed of the mixed salt solution is 10L / min, the dropping speed of the precipitant solution is 20L / min, and the dropping speed of the complexing agent solution is 20L / min. Add dropwise until the mixed salt solution is added completely. The reaction pH value is controlled at 12 and the reaction is carried out for 20h. After the reaction is completed, filter and separate the precursor, wash, dry and set aside.

[0113] S4. The precursor and the lithium source are mixed evenly and sintered. First, the furnace temperature is raised to a sintering temperature of 550°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 12 hours to obtain the positive electrode material.

[0114] Comparative Example 2

[0115] A method for preparing a positive electrode material for a battery, comprising the following steps:

[0116] S1. Weigh a nickel source, a cobalt source, and a manganese source at a molar ratio of 8:1:1 between nickel, cobalt, and manganese; weigh a lithium source at a molar ratio of 1.1:1 between the molar number of lithium and the total molar number of nickel, cobalt, and manganese; divide the nickel source into two parts of unequal weight, wherein the weight ratio of the larger part to the smaller part is 9:1;

[0117] S2. Preparation of a large weight portion of nickel source solution: dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0118] Preparation of cobalt source solution: dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L;

[0119] Manganese source solution preparation: dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L;

[0120] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0121] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0122] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0123] S3. Open a reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, add the mixed salt solution of nickel, cobalt and manganese source solution, the precipitant solution, and the complexing agent solution dropwise into the reactor to react. The dropping speed of the mixed salt solution is 10L / min, the dropping speed of the precipitant solution is 20L / min, and the dropping speed of the complexing agent solution is 20L / min. Add dropwise until the mixed salt solution is added completely. The reaction pH value is controlled at 12 and the reaction is carried out for 20h. After the reaction is completed, filter and separate the precursor, wash, dry and set aside.

[0124] S4, the precursor and the lithium source are mixed evenly and sintered for the first time, the furnace temperature is first raised to a sintering temperature of 550°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 12 hours to obtain a first sintered product;

[0125] S5. Preparation of a small weight portion of nickel source solution: dissolving nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0126] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0127] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0128] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0129] S6. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction bottom liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor. The dropping rate of the nickel salt solution is 3L / min, the dropping rate of the precipitant solution is 6L / min, and the dropping rate of the complexing agent solution is 6L / min. The nickel salt solution is added dropwise until the nickel salt solution is added completely, and the reaction is carried out. The reaction pH value is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, washed, and dried for standby use.

[0130] S7. According to the weight ratio of zirconia to nickel precipitate being 0.2:1, ball-mill the nickel precipitate, zirconia and the first sintered product. Set the ball-milling time to 4 h and the ball-milling speed to 400 rpm. After mixing evenly, raise the furnace temperature to the sintering temperature of 700 °C at a heating rate of 4 °C / min, and then maintain the sintering time at the set temperature for 10 h to obtain the battery cathode material.

[0131] Comparative Example 3

[0132] A preparation method of a battery cathode material, the steps of which include:

[0133] S1. Weigh nickel source, cobalt source, and manganese source according to the molar ratio of nickel, cobalt, and manganese being 8:1:1; weigh the lithium source according to the molar ratio of the lithium molar number to the total molar number of nickel, cobalt, and manganese being 1.1:1; divide the nickel source into two parts with unequal weights, and the weight ratio of the large weight part to the small weight part is 9:1.

[0134] S2. Preparation of the large weight part of the nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L.

[0135] Preparation of the cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L.

[0136] Preparation of the manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L.

[0137] Preparation of the reaction bottom liquid: Mix ammonia water and deionized water according to the volume concentration of ammonia water being 3%, and the mass concentration of ammonia water being 28%.

[0138] Preparation of the precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%.

[0139] Preparation of the complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%.

[0140] S3. Start the reaction kettle equipped with a three-dimensional paddle stirring device, flush nitrogen into the kettle, and add 50 L of the reaction bottom liquid. Under the conditions of stirring at 400 rpm and a temperature of 40 °C, simultaneously drop the mixed salt solution of the nickel-cobalt-manganese source solution, the precipitant solution, and the complexing agent solution into the reaction kettle for reaction. The dropping speed of the mixed salt solution is 10 L / min, the dropping speed of the precipitant solution is 20 L / min, and the dropping speed of the complexing agent solution is 20 L / min. Drop until the mixed salt solution is completely dropped, control the reaction pH value at 12, react for 20 h, filter after the reaction ends, separate the precursor, wash and dry it for standby.

[0141] S4, the precursor and the lithium source are mixed evenly and sintered for the first time, the furnace temperature is first raised to a sintering temperature of 550°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 12 hours to obtain a first sintered product;

[0142] S5. Preparation of a small weight portion of nickel source solution: dissolving nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L;

[0143] Reaction base solution preparation: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 3% and the mass concentration of ammonia water of 28%;

[0144] Preparation of precipitant solution: Mix sodium hydroxide and deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%;

[0145] Complexing agent solution preparation: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%;

[0146] S6. Open the reactor with a three-dimensional paddle stirring device, flush nitrogen into the reactor, and add 50L of reaction bottom liquid. Under the conditions of stirring at 400rpm and a temperature of 40°C, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor. The dropping rate of the nickel salt solution is 3L / min, the dropping rate of the precipitant solution is 6L / min, and the dropping rate of the complexing agent solution is 6L / min. The nickel salt solution is added dropwise until the nickel salt solution is added completely, and the reaction is carried out. The reaction pH value is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, washed, and dried for standby use.

[0147] S7. Preparation of catechol solution: dissolve catechol in a mixed solution of deionized water and ethanol in a volume ratio of 2:1, with a concentration of 2 g / L; the weight ratio of catechol to nickel precipitate is 0.5:1;

[0148] S8, adding the nickel precipitate to the catechol solution, adding sodium hydroxide to adjust the pH value of the solution to 9, and reacting under the conditions of stirring at 400 rpm and a temperature of 50° C. for 12 hours. After the coating is completed, filtering and separating the solid, washing, and drying it for later use;

[0149] S9. Ball mill the solid product of S8 and the first sintering product. The ball milling time is set to 4 hours, and the ball milling speed is controlled at 400 rpm. After mixing evenly, the furnace temperature is raised to a sintering temperature of 700°C at a heating rate of 4°C / min, and then the sintering time is maintained at the set temperature for 10 hours to obtain the battery positive electrode material.

[0150] In order to verify the beneficial effects of the present invention, it is necessary to test the positive electrode materials obtained in the above embodiments and comparative examples.

[0151] Test items: Test the original nickel-lithium mixing rate of the positive electrode material, that is, the nickel-lithium mixing rate before assembly; then use the positive electrode material to assemble into a battery, perform fast charge cycles on the battery, and then disassemble and test the nickel-lithium mixing rate of the positive electrode material after the fast charge cycle.

[0152] Battery assembly: The positive electrode material, conductive agent SuperP, and binder PVDF were dissolved in nitrogen methyl pyrrolidone (NMP) in a mass ratio of 8:1:1 to prepare a slurry. The slurry was coated on aluminum foil using an automatic coating machine. After vacuum drying for 12 hours, the positive electrode sheets were cut into pieces. The button cells were assembled using general process conditions. The button cell specifications were CR2023, the negative electrode was a lithium sheet, the separator was a polypropylene film, the electrolyte solvent was a 1:1 volume ratio of EC / DEC mixed solvent, the conductive salt was 1M lithium hexafluorophosphate, the button cell packaging pressure was 800Pa, and the packaging time was 5 seconds.

[0153] Test batteries were assembled using the positive electrode materials of Examples 1-3 and Comparative Examples 1-3 according to the above battery assembly method. Three test batteries were made for each set of Examples or Comparative Examples.

[0154] Each test group consisted of three test cells, one of which completed 50 constant-current charge-discharge cycles, one completed 100 constant-current charge-discharge cycles, and one completed 200 constant-current charge-discharge cycles. Test conditions were 40°C, 4.6-3.0V voltage range, 3C charge / 0.3C discharge. Capacity retention and nickel-lithium mixing rate were measured over the test cycles.

[0155] Nickel-lithium mixed arrangement detection: X-ray diffraction (XRD) detection is used; pre-assembly detection directly prepares samples of the positive electrode material for testing; post-assembly detection requires disassembling the battery to separate the positive electrode material, grinding the positive electrode material and drying it at 70°C for 10 hours before preparing samples for testing;

[0156]

[0157] It can be seen from the above test results that the nickel ion mixing rate of Examples 1-3 after fast charging test is significantly lower than that of Comparative Examples 1-3. Therefore, it can be seen that the technical solution of the present invention can effectively reduce the occurrence of nickel ion mixing phenomenon.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-throughput power battery positive electrode material, characterized in that: The steps include: Step 1, weigh the nickel source, cobalt source, manganese source and lithium source, and divide the nickel source into two parts of unequal weight for later use; Step 2: Prepare solutions of nickel source, cobalt source and manganese source in large weight portions respectively, and mix the solutions of the three to form a mixed salt solution; add the reaction base liquid to the reactor, and under stirring, dropwise add the mixed salt solution, precipitant solution and complexing agent solution into the reactor at the same time to react, and control the reaction pH value to be 10-12. After the reaction is completed, filter to separate the precursor, wash and dry it for later use; Step 3, mixing the precursor and the lithium source uniformly and performing a first sintering to obtain a first sintering product; Step 4, a small amount of nickel source is configured into a nickel salt solution; a reaction base liquid is added to a reactor, and under stirring, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor for reaction, and the reaction pH value is controlled at 10 to 12. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, and the nickel precipitate is washed and dried for later use; Step 5, adding the nickel precipitate to the catechol solution, adjusting the solution to alkalinity, reacting under stirring, and after the coating is completed, slowly adding the zirconium dioxide suspension under stirring to continue the reaction, filtering and separating the solid after the reaction is completed, washing, drying and setting aside; Step 6: Evenly mix the solid product obtained in step 5 and the first sintered product obtained in step 3 and sinter them to obtain a high-throughput power battery positive electrode material; In step 1, a nickel source, a cobalt source, and a manganese source are weighed according to a molar ratio of nickel, cobalt, and manganese of 5 to 8:1 to 2:1 to 3; a lithium source is weighed according to a molar ratio of lithium moles to the total molar number of nickel, cobalt, and manganese of 1 to 1.1:1; the nickel source is divided into two parts of unequal weight, wherein the weight ratio of the large weight part to the small weight part is 7 to 9:1; the nickel source is selected from nickel sulfate or nickel nitrate, the cobalt source is selected from cobalt sulfate or cobalt nitrate, the manganese source is selected from manganese sulfate or manganese nitrate, and the lithium source is selected from lithium carbonate; In step 2, the concentration of the nickel source solution is 1-1.5 mol / L; the concentration of the cobalt source solution is 0.8-1 mol / L; and the concentration of the manganese source solution is 1-1.2 mol / L.

2. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In steps 2 and 4, Reaction base solution configuration: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 1% to 3%, and the mass concentration of ammonia water is 25% to 28%; Precipitant solution configuration: sodium hydroxide aqueous solution with a mass concentration of 25% to 30%; Complexing agent solution preparation: ammonia water with a mass concentration of 15% to 20%.

3. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 2, the mixed salt solution is added at a rate of 5 to 10 L / min, the precipitant solution is added at a rate of 10 to 20 L / min, and the complexing agent solution is added at a rate of 5 to 20 L / min until the mixed salt solution is completely added.

4. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step three, the first sintering temperature is 500-550°C. First, the furnace temperature is raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 10-12 hours. In step six, the second sintering temperature is 600-700°C. First, the furnace temperature is raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 8-10 hours.

5. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 4, the nickel salt solution is added at a rate of 1 to 3 L / min, the precipitant solution is added at a rate of 2 to 6 L / min, and the complexing agent solution is added at a rate of 1 to 6 L / min until the nickel salt solution is completely added.

6. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: Preparation of the catechol solution in step 5: dissolving catechol in a mixed solution of deionized water and ethanol in a volume ratio of 1 to 2:1, the concentration of the catechol solution is 1 to 2 g / L; the weight ratio of catechol to nickel precipitate is 0.1 to 0.5:1; Configuration of zirconium dioxide suspension: dispersing nano-scale zirconium dioxide in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.1-0.2:1; the weight ratio of zirconium dioxide to deionized water is 1:40-80.

7. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 5, the coating reaction temperature is 30-50°C, and the reaction time is 8-12h; the zirconium dioxide modification reaction temperature is 40-60°C, and the reaction time is 4-6h.

8. A high-throughput power battery positive electrode material, characterized in that: The high-throughput power battery positive electrode material is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-performance lithium ion battery ternary positive electrode material and preparation method thereof

    CN110581272A

  • Preparation method of Li2TiO3 and Li2ZrO3 composite coated ternary cathode material

    CN112447946A